IBU Coaching Framework (2025)
Coaches play an essential role in promoting biathlon participation and the development of athletes and teams. According to the International Council for Coaching Excellence (ICCE) reviews, coaching is in its most dynamic era in history. Coaches work with increasingly diverse populations and face heightened demands from athletes, their athletes` parents, the administration, and fans. Coaches are required to fulfill various roles, including educator, guide, sports psychologist, and business manager. Coaches are asked to emphasize positive interaction and athletes` overall development at a higher level of competition than simply win-loss records0F. Coaches have a responsibility to improve and expand their capabilities on an ongoing basis to fully meet the needs of the athletes they serve and work with. As an international federation, we understand the need to strengthen coaches` long-term development and the responsibility for delivering coaching education in cooperation with NFs and educational partners. We believe that the global flow of knowl- edge, information, and research about biathlon coaching allows us to preserve and develop more systematically and sustainably. The IBU Coaching Framework (IBUCF) supports developing and professionalizing biathlon coaches in different countries and should assist in coaching recognition and certification. The IBUCF is also a work in progress and will evolve, as does the coaching profession following athletes` needs and our discipline demands.